Bibliometric Analysis of Behavioral Finance - KMT Lasmiatun; Rival Pahrijal; Ilham Akbar Bunyamin (West Science Social and Humanities Studies, 2026)
Behavioral finance has emerged as a prominent research field that challenges the traditional assumption of investor rationality by incorporating psychological, cognitive, and emotional factors into financial decision-making. This study aims to map the intellectual structure, research trends, and collaborative patterns within behavioral finance literature through a bibliometric analysis. Data were collected from the Scopus database and analyzed using VOSviewer to examine keyword co-occurrence, overlay visualization, density visualization, co-authorship networks, institutional collaboration, country collaboration, and citation performance. The results reveal that behavioral finance, finance, and decision making constitute the core themes of the field, with strong associations to investor sentiment, behavioral biases, financial literacy, risk perception, and investment behavior. Overlay visualization indicates a recent shift toward technology-oriented topics such as artificial intelligence, machine learning, blockchain, and data mining, reflecting the increasing integration of digital technologies into financial research. The co-authorship and collaboration analyses demonstrate that research activities are concentrated among a limited number of influential authors, institutions, and countries, particularly the United States, China, the United Kingdom, India, and Australia. Citation analysis highlights the enduring influence of seminal works on investor behavior, financial literacy, market efficiency, and social media sentiment. The findings suggest that behavioral finance has evolved into a multidisciplinary and globally connected research domain with expanding opportunities in fintech, digital finance, sustainable investing, and artificial intelligence applications. This study contributes to a comprehensive understanding of the development and future directions of behavioral finance research.